Ice flow modulated by tides at up to annual periods at Rutford Ice Stream, West Antarctica - Murray, T; Smith, AM; Matt King; Weedon, GP (2007)
For over 2-years we have collected GPS data âˆ¼40 km upstream of the grounding line on Rutford Ice Stream, West Antarctica. Here we examine deviations from mean downstream flow. Although the record is incomplete during winter, there is clear modulation of flow at semi-diurnal, diurnal, two-weekly, semi-annual, and annual ocean tidal frequencies. This is the first observation of ice stream flow variations over such a long time-period, and such a wide range of frequencies. The ice stream flows fastest at equinoxes when there are two semi-diurnal tides of equal magnitude, and slowest at solstices when one of the semi-diurnal tides has lower amplitude. The sensitivity of the downstream flow is greatest to the long-period forcing, which suggests that ice stream velocity may be affected by future changes in sea level. If so, this effect would provide a feedback whereby rising sea levels could increase ice stream velocity and hence discharge. Copyright 2007 by the American Geophysical Union.